Innovative Systems to Deliver Allergen Powder for Epicutaneous Immunotherapy - Wang, Yensheng; Kong, Yifei; Wu, Mei X. (Frontiers in Immunology, 2021)
ABSTRACT Allergy is a disorder owing to hyperimmune responses to a particular kind of substance like food and the disease remains a serious healthcare burden worldwide. This unpleasant and sometimes fatal allergic disease has been tackled vigorously by allergen-specific immunotherapy for over a century, but the progress made so far is far from satisfactory for some allergies. Herein, we introduce innovative, allergen powder-based epicutaneous immunotherapies (EPIT), which could potentially serve to generate a new stream of technological possibilities that embrace the features of super safety and efficacious immunotherapy by manipulating the plasticity of the skin immune system via sufficient delivery of not only allergens but also tolerogenic adjuvants. We attempt to lay a framework to help understand the immune physiology of the skin, epicutaneous delivery of powdered allergy, and potentials for tolerogenic adjuvants. Preclinical and clinical data are reviewed showing that deposition of allergen powder into an array of micropores in the epidermis can confer significant advantages over intradermal or subcutaneous injection of aqueous allergens or other epicutaneous delivery systems to induce immunological responses toward tolerance at little risk of anaphylaxis. Finally, the safety, cost-effectiveness, and acceptability of these novel EPITs are discussed, which offers the perspective of future immunotherapies with all desirable features.